About the Contributors - Editorial Board, The Archive (The Archive; Vol 17 (2021): Special Publication No. 17: Selected Papers from the 14th Philippine Linguistics Congress, 2022)
April Almarines holds a Bachelor of Science degree in Public Health from the University of the Philippines Manila. She has been working as a translator and project manager for several non-profit organizations and activities, advocating drug prevention education programs, human rights awareness, religious tolerance, campaigns to eradicate illiteracy, and other similar activities. She has been a contributor to the Austronesian Comparative Dictionary started by Robert A. Blust. She was also mentored by R. David Zorc in synchronic, comparative, and historical linguistics, and is currently working on a project involving Tagalog etymologies. Jeconiah Dreisbach is a lecturer at the Filipino Department of De La Salle University where he teaches interdisciplinary courses in language, culture, and media studies. Concurrently, he is doing his PhD specializing in critical sociolinguistics at the Universitat Oberta de Catalunya in Barcelona and is part of the Language, Culture and Identity in the Global Age (IdentiCat) research group. For his contributions as a Mindanaoan researcher in Philippine cultural studies, Jecon was recently appointed as an Honorary Research Fellow of the Office of Policy Research of the Bangsamoro Parliament. Maria Kristina Gallego is Assistant Professor at the Department of Linguistics, University of the Philippines Diliman. She is currently taking her PhD at the School of Culture, History and Language, at the Australian National University, with a documentation grant from the Endangered Languages Documentation Programme (ELDP). She has done fieldwork in various communities across the Philippines, and has published papers on Philippine culture history, language structure, and language change. Her main research interest lies on historical linguistics, specifically on the descent and genetic relationship of the Philippine languages. She investigates this from the perspective of language contact, with her PhD project focusing on the contact between speakers of Ibatan and Ilokano on the small island community of Babuyan Claro in the far north of the Philippines. Diane Manzano is Assistant Professor at the Department of Humanities, University of the Philippines Los Baños. She has taught Wika 1 (Language, Culture, and Society) at the same university and obtained her Master of Arts in Linguistics degree from the University of the Philippines Diliman. Her master’s thesis deals with the description of the grammar of Inati, spoken in the island of Panay. Vincent Christopher A. Santiago is currently an instructor and graduate student at the UP Department of Linguistics. His research interests include language documentation and description, acoustic phonetics, and dialectology. Currently, he is working on a grammatical description of Porohanon spoken in the Camotes Islands, Cebu, Philippines. He has presented his research in the Southeast Asian Linguistics Society Conference, the Philippine Linguistics Congress, and various other conferences and colloquia. He is also a member of the Linguistics Society of the Philippines. Ruanni Tupas teaches sociolinguistics in education at the Department of Culture, Communication and Media, Institute of Education, University College London. He is an Associate Editor of the International Journal of the Sociology of Language. Prior to his current position, he taught at the University of the Philippines in Diliman, National Institute of Education, Singapore, and the National University of Singapore. R. David Zorc has been blessed with over 40 years of experience in comparative-historical linguistics, lexicography, language teaching, language analysis, curriculum development, and applied linguistics. He has conducted research on 80 languages of the Philippines, Aboriginal Australia, Armenia, and Africa, encompassing the Austronesian, Bantu, Cushitic, Indo-European, and Pamañ Nyungan language families. His publication of 31 books on 24 languages, 40 journal articles, and 30 presentations at international conferences solidifies his reputation as one of the world’s leading authorities on the less-commonly taught languages, especially of the Philippines. He has produced six dictionaries (Aklanon, Eastern Armenian, Somali, Tagalog Slang, Filipino Etymological, and Yolngu Matha). He was awarded the Brother Andrew Gonzalez, FSC Distinguished Professorial Chair in Linguistics and Language Education by the Linguistic Society of the Philippines on February 26, 2005. Louward Allen Zubiri is a PhD student at the University of Hawai‘i at Mānoa and a student affiliate of East-West Center. He finished his BA and MA in Linguistics at the University of the Philippines Diliman. His research interests are in the areas of description, documentation, and revitalization of non-dominant and/or scarcely described Philippine languages and scripts. He is interested in how description, documentation, and revitalization are informative of and interdependent with policymaking, education, community development, and heritage awareness. He has undertaken community engagements with a focus on advocacy, training, and research on, for, and with Indigenous Cultural Communities in the Philippines. He is a member of the Linguistic Society of America, the Linguistic Society of Hawai‘i, the Linguistic Society of the Philippines, and Pi Gamma Mu International Honor Society.